Humanizing the Non-Human Animal: Framing the Analysis of Dogs’ Rights Movement in Indonesia - Resolute, Prisilia (Masyarakat: Jurnal Sosiologi, 2016)
The consumption of dog meat has been a common practice in the past few decades and a symbol for certain groups all around the world. Dogs Are Not Food (DANF) is a new social movement aimed to ban dog meat consumption, initiated by several animal rights organizations in Indonesia. The campaign seems to be self-contradictory: why ban the consumption of dog meat while still allowing the consumption of meat from other animals? Drawing on framing analysis, this article uses participant observation and in-depth interview with some self-identified animal activists and/or supporters of DANF. In contrast to previous studies, which are too critical of DANF, this article gives a sociological explanation on the functions of dogs in society and analysis of DANF’s framing. I argue that the framing used by the movement attempts to humanize non-human animals. Banning consumption of dog meat, therefore, is the goal of the DANF campaign.